Ladies and Gentlemen - Cobb, Irvin S. (Irvin Shrewsbury), 1876-1944 (Salt Lake City, UT : Project Gutenberg, 2014)
"Ladies and Gentlemen" by Irvin S. Cobb is a collection of humorous sketches and tales written in the late 1920s. The work captures the vibrancy and quirks of Southern life, particularly during events like the annual reunion of Confederate veterans. Through various characters, Cobb illustrates the charm and eccentricities that define his subjects, offering a significant commentary on the cultural and historical backdrop of the South during that era. The opening of the collection sets the stage at a bustling reunion, where the aging veterans are prominently featured alongside a multitude of enthusiastic women attending the festivities. The narrative introduces the weary yet spirited character of Nathan Braswell, an aged Confederate soldier navigating his way through the reunion's chaos with the help of a young Boy Scout. As Braswell struggles with the exhaustion of age amidst the lively environment, we see glimpses of his reminiscences about the past and the relationships formed during the war. The early chapters highlight themes of nostalgia, the passage of time, and the interactions between generations, creating a rich tapestry of Southern culture that Cobb keenly observes and conveys. (This is an automatically generated summary.)
A lady and a gentleman -- The order of the bath -- Two of everything -- We of the Old South -- Killed with kindness -- Peace on earth -- Three wise men of the East Side -- The cowboy and the lady and her pa -- A close shave -- Good Sam -- How to choke a cat without using butter.
Release date is 2014-04-05
E-text prepared by eagkw, David E. Brown, Bryan Ness, and the Online Distributed Proofreading Team (http://www.pgdp.net)
Keywords: Fiction; Short stories, American